Online industrial sales and support system - Liew, Wei Bing (2011)
Online Industrial Sales and Support System is an online web base management system to manage industrial machine sales and support for MID Mechatronic Sdn Bhd.The current system of the company is old traditional filing system to record the customers,sales,appointment and do not have a proper management system used and lack of proper platform for support and problem solving solution for customers. Therefore this system is developed to manage sales services and to develop an advisory for technical problems.There are two targeted users in this system,which are the admin staff and the customers of MID Mechatronic Sdn Bhd.This system has total of eleven main modules in this system, which is login and registration,customize machine specification, make appointment and order,manage order and profile,search and download support,forum interaction for the customer side function and manage registered customer,manage machine and specification,approve order and appointment,manage and upload support,forum administration for admin side function. Rapid Application Development (RAD) model is used to develop this project.There are four phases which are requirements planning,user design,construction and cutover.The implementation of interface and coding to each module in the system is completed.The testing shows that the acceptance criteria of the system are fulfilled with the requirements that are set earlier.This system succeeds to achieve the objectives and solve the problems stated earlier.